Ahmad Javed’s Symbolic Strategies in Short Stories - Khan, Imran; Gondal, Ghulam Abbas (Makhz (Research Journal), 2025)
In the early era of Urdu short story the trend of realism, romanticism and exemplification remained dominant but besides that symbolic short stories have also been written every now and then. In 1960, symbolism appeared as a clear and flourished trend Ahmad Javed is also counted among symbolist short story writers. He expressed the political, social and economic problems of his time through symbolic style and technique. The effects on humans resulted by political suppression of martial law were only be expressed through symbolism. In this article, the symbolic implication of Ahmad Javed will be discussed.